Catalog of Anaedus Blanchard, 1842 with nomenclatural notes (Coleoptera: Tenebrionidae: Lagriinae) - Kanda, Kojun; Johnston, M. Andrew (Zootaxa, 2024)
The genus Anaedus Blanchard, 1842 in the tribe Goniaderini Lacordaire, 1859 has experienced drastic genus-level change where seven other genera were subsumed as synonyms by Aalbu et al. (2023). That study addressed multiple nomenclatural issues including several replacement names, but did not provide a full species-group catalog. This study presents a full catalog for the 142 species-group names currently belonging to Anaedus and rectifies several nomenclatural issues missed within the previous study. The catalog includes full nomenclatural histories and type localities for all taxa. The following New Combinations are established: Anaedus keralensis (Kaszab, 1979), An. madrensis (Kaszab, 1979), An. philippinus (Schawaller, 1994), An. setosus (Kaszab, 1979), An. simillimus (Kaszab, 1979). The following New Replacement Names are established for the species listed in parentheses: Anaedus fairmairei Kanda & Johnston (replaces An. fulvipennis Fairmaire, 1889), An. pici Kanda & Johnston (replaces An. rufipes Pic, 192), An. pictus Kanda & Johnston (replaces Spinolyprops maculatus Kulzer, 1954), An. neorufescens Kanda & Johnston (replaces Aspisoma rufescens Pic, 1951).